TERMINOLOGICAL METAPHORIZATION AND ITS MAIN TYPES (International Congress on Economics, Management and Business Studies, 2026)
Metaphors in terminology operate through specific cognitive models. The theory of “mapping” proposed by George Lakoff and Mark Johnson demonstrates that structures of thought are transferred from one experiential domain to another.“Within terminological nomination, the process of metaphorization enriches the vocabulary by assigning new meanings to already existing linguistic units. This method plays a crucial role in transferring words from everyday language into the scientific and technical sphere.”